The Influence of Integrated Value in Purchasing Game Item and Game Satisfaction against Game Item Purchase Intention over the Unknown's Battlegrounds Player - Ardian Pramana Wicaksana; Tantri Yanuar Rahmat Syah (Penerbit Kemala Indonesia, 2020)
The existence of online gaming as entertainment is inseparable from the rapid development of technology that allows an online battle games to be used at any time. In this study, we determine the effect of integrated value of purchasing game items and satisfaction about games on game item purchase intentions by examines the respondents of the game Player Unknown's Battle Grounds and involves as many as 200 respondents using the Structural Equation Modelling (SEM) method. The results showed that there was a relationship between integrated values of purchasing game items against satisfaction about game, there was a relationship between integrated value of purchasing game items on game item purchase intentions, there was a relationship between satisfaction about game and game item purchase intentions. And satisfaction about game mediates the relationship between integrated value of purchasing game items and game item purchase intentions